Odpowiedzi

2010-01-07T15:07:06+01:00
A)
3x=12
x=1-y

3(1-y)=12
x=1-y

3-y=12
x=1-y

-y=9|:-1
x=1-y

y=-9
x=10

b)
5y=2|:5
x+y=2,4

y=0.5
x+0,5=2,4

y=0,5
x=2,4-0,5

y=0,5
x=1,9

c)
4y-x=6
17y=0

4y-x=6
y=-17

4*(-17)-x=6
y=-17

-68-x=6
y=-17

-x=74|:(-1)
y=-17

x=-74
y=-17
2010-01-07T15:11:54+01:00
A) x= 4
4-y=1
x=4
y=-3

b) y= 0.4
x+0.4=2.4
y=0.4
x=2

c) ...

d) a = 3
b = 3

e) u=4v
5 ( 4v ) - v= 10
u= 4v
19 v= 10 |: 19
u= ...
v = 10/19
u= 10/19 razy 4
v= 10/19

f) s= r/3

3( r/3) + s = 24
r+s = 24

r= 4
s= 12